2017
DOI: 10.2174/1874192401711010066
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Familial Hypercholesterolemia (FH) in Saudi Arabia: Prime Time for Patient FH Registry

Abstract: Background:Familial hypercholesterolemia (FH) is a life-threatening inherited condition. Untreated patients have the risk to develop raised plasma levels of cholesterol, atherosclerosis and cardiovascular disease (CVD). If diagnosed and treated early in life, the pathological consequences due to atherosclerosis could be avoided and patients with FH can have an anticipated normal life. Mounting evidence suggests that FH is underdiagnosed and undertreated in all populations. The underlying molecular basis of FH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…A strong pre-registry campaign (e.g. in the media) can achieve these objectives, and could identify any cultural barriers hindering the establishment of a registry [ 36 ]. Also, the results of this registry can be fed back to physicians in the form of publications, audits, and conferences to engender a more personalized approach to improving patient care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A strong pre-registry campaign (e.g. in the media) can achieve these objectives, and could identify any cultural barriers hindering the establishment of a registry [ 36 ]. Also, the results of this registry can be fed back to physicians in the form of publications, audits, and conferences to engender a more personalized approach to improving patient care.…”
Section: Discussionmentioning
confidence: 99%
“…FH registry can help in determining the genetic predisposition of such condition which would help in providing an early intervention. Also, it will enable identifying the most common disease-causing mutations among the Saudi population and identify population specific novel mutations helping in future rapid molecular diagnosis [ 36 ]. The researchers can access de-identified data of FH database through research ethics committees or the consultative body to determine the burden of disease, and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In Saudi Arabia, there are inadequate numbers of reports available for prevalence and molecular characteristics of FH. 4,[8][9][10][11][12][13][14][15] The disease may have a higher prevalence in Saudi Arabia than in other neighboring countries because consanguineous marriages exceeding 55% 16,17 and due to the lack of national registries and genetic screening programmes for FH, the disease is under diagnosed and under estimated. In the present study, we performed WES of FH patient, shown to be negative for LDLR mutation.…”
Section: Introductionmentioning
confidence: 99%